Bradycardia during Transradial Cardiac Catheterization due to Catheter Manipulation: Resolved by Catheter Removal - Maheedhar Gedela; Vishesh Kumar; Kashif Abbas Shaikh; Adam Stys; Tomasz Stys (Case Reports in Vascular Medicine)
Purpose. To report the resolution of bradycardia encountered during transradial cardiac catheterization through the catheter pullback technique in two cases. Case Report. A 62-year-old male and an 81-year-old male underwent coronary angiogram to evaluate for coronary artery disease and as a result of positive stress test, respectively. Upon engagement of the FL 3.5 catheter into the ascending aorta through the transradial approach, the first case developed bradycardia with a heart rate of 39 beats per minute. The second case developed profound bradycardia with a heart rate of 25 beats per minute upon insertion of the 5 Fr FL 3.5 catheter near the right brachiocephalic trunk through the right radial access. Conclusion. Bradycardia can be subsided by removal of the catheter during catheter manipulation in patients undergoing transradial coronary angiogram if there is a suspicion of excessive stretching of aortic arch receptors and/or carotid sinus receptors.